ANALISIS PENGELOLAAN AIR PROGRAM PAMSIMAS SEBAGAI SUMBER AIR BERSIH DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Revi Lasmita; Aras Mulyadi; Manyuk Fauzi (Program Pascasarjana Universitas Riau, 2020)
Clean water according to Permenkes RI No 416 / Menkes / Per / IX / 1990 is water that used for daily needs whose quality meets health requirements and can be drunk after cooking, one of the government's efforts to meet the clean water needs of the community is the Pamsimas Program. The Pamsimas Program is one of the programs and concrete actions of the government (central and regional) with the support of the World Bank to improve and meet the needs of drinking water supply, sanitation to improve the level of public health, especially in reducing the number of diarrheal diseases and other diseases that are transmitted through water and the environment. Muaro Tombang Village, Sungai Manau Village and Bukit Kauman Village are the three villages in Kuantan Mudik Sub-District that have not had access to 100% clean water. Indicators of success and sustainability of the Pamsimas Program are the quantity and quality of water sources, management policies and management strategies for the Pamsimas Program. The quantity of water in the three villages in terms of discharge and minimum reservoir capacity meet the needs of the community, the water quality in the three villages there are several parameters that do not meet the quality standards of the Minister of Health Regulation No. 416 of 1990 concerning Clean Water Quality Requirements, so it needs to be treated for water Pamsimas Program. The community's perception of the socio-economic and management policies of the Pamsimas Program Muaro Tombang Village and Sungai Manau Village is included in the agreed category, while the community's perception of the socio-economic and management policy of the Pamsimas Program in the Bukit Kauman Village is in the neutral category. The right strategy used for the management of the Pamsimas Program in the three villages is the aggressive strategy (Growth Oriented Strategy), namely the development of the Pamsimas Program by utilizing the strengths of the opportunities that have been identified.